Isometry of the subspacesof solutions of systems of differential equations to the spaces of real functions - Imash kyzy, M.; Abdullayev, F. G.; Bushev, D. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We determine the subspaces of solutions of the systems of Laplace and heat-conduction differential equations isometric to the corresponding spaces of real functions determined on the set of real numbers.